2010
DOI: 10.1016/s2255-4971(15)30430-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Complementary Exams in the Diagnosis of Rotator Cuff Injuries

Abstract: The aim of this study was to evaluate the accuracy of simple radiography, ultrasound and magnetic resonance imaging (MRI) in diagnosing rotator cuff injuries, comparing their findings with open or arthroscopic surgery findings. Methods: Protocols of the Shoulder and Elbow Surgery Service for patients undergoing surgical treatment for rotator cuff injuries diagnosed by means of radiography, ultrasound and/or MRI between 2002 and 2007 were evaluated. Based on the data gathered, we analyzed the sensitivity, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“… 24 25 26 To close the diagnosis of complete or partial RC injury, a musculoskeletal ultrasound examination was performed bilaterally in all patients, using the protocol established by Selvaraj et al 27 Ultrasonography is a reliable method, presenting high accuracy in the diagnosis of RC lesions. 28 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 24 25 26 To close the diagnosis of complete or partial RC injury, a musculoskeletal ultrasound examination was performed bilaterally in all patients, using the protocol established by Selvaraj et al 27 Ultrasonography is a reliable method, presenting high accuracy in the diagnosis of RC lesions. 28 …”
Section: Methodsmentioning
confidence: 99%
“…[24][25][26] To close the diagnosis of complete or partial RC injury, a musculoskeletal ultrasound examination was performed bilaterally in all patients, using the protocol established by Selvaraj et al 27 Ultrasonography is a reliable method, presenting high accuracy in the diagnosis of RC lesions. 28 The physical examinations of the volunteers were performed by a physician with residency in orthopedics and traumatology, specialized in shoulder/elbow surgery, at the endocrinology and obesity outpatient clinic of our institution. The imaging examinations were performed by a physician specialized in musculoskeletal ultrasonography, with a diploma issued by Associação Médica Brasileira in the field of radiology and diagnostic imaging.…”
Section: Data Collected and Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has up to 92% sensitivity and 94% specificity in detecting complete rotator cuff tear, [ 14 ] and prior studies have established and validated application of high-frequency probe MU in the diagnosis of rotator cuff tear and rotator cuff injury. [ 15 ] El-Kouba et al [ 16 ] confirmed the accuracy and sensitivity of MU in diagnosing abnormal rotator cuffs. Research into the ultrasonographic characteristics of the shoulder in stroke patients revealed that ultrasonography was helpful in detecting soft tissue lesions in these patients.…”
Section: Introductionmentioning
confidence: 99%